FEATURES OF DEVELOPMENT, COURSE AND TREATMENT OF JAW PERIOSTITIS IN CHILDREN . - AKHMEDOV ILKHOM IBROHIMOVYCH (TADQIQOTLAR.UZ, 2024)
ABSTRACT It is known that the diagnosis and treatment of inflammatory diseases of the maxillofacial region represent one of the main problems in pediatric dentistry. According to a number of researchers, inflammatory diseases of the maxillofacial region account for up to 21% of all surgical and 52% of dental diseases in childhood. The course of odontogenic infection in children has a number of features due to the relative immaturity of the child’s organs and tissues, imperfect immunity, abundance of lymphatic tissue, the presence of anatomical and physiological features of the structure of teeth and jaws, ease of damage and increased permeability of natural protective barriers to microbes, etc.